Mediastinal paraganglioma: time to panic?. (23rd February 2011) - Parisinos, Constantinos A; Carnochan, Fiona M; Gregoriades, Maria L; Monaghan, Hannah; Patel, Dilip; Walker, William S
Abstract : Paragangliomas (extra-adrenal phaeochromocytomas) are tumours arising from extra-adrenal chromaffin tissue. The authors describe a case of a 54-year-old woman presenting with shortness of breath and chest pain. CT pulmonary angiogram demonstrated a mediastinal mass. Further history taking revealed spontaneous attacks of headaches and palpitations. Subsequent imaging and biochemical testing confirmed the presence of a rare posterior mediastinal paraganglioma. The patient was prepared for surgery. A left thoracolaparotomy was performed and the mass was excised in its entirety. Postoperatively, 24-h urine collections showed normal normetanephrine and metanephrine levels. Since then, yearly catecholamine levels remain within the normal range.